En los orígenes del federalismo mexicano. Problemas historiográficos recientes - Tecuanhuey, Alicia (Revista Complutense de Historia de América, 2008)
In this article I intend to reflect on the recent interpretations by the mexicanist historiography devoted to the study of the establishment of federalism in Mexico. Focus is centered in the proposals which review the predominant positions in order to recognize the historical problems entwined in them and to depict their interpretative horizons and perspectives. I would like to emphasize that the historians dealt with here developed a program that suggests new ways of approaching research. As in all processes, which usually are full of accidents and disagreements, the results, now in ours hands, are exciting. Continuity and discontinuity, long and short duration, multicausality are current preoccupations of historians. The field of the study is extended and is most complex.